2020
DOI: 10.1101/2020.05.14.095539
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Artificial neural networks for monitoring network optimisation—a practical example using a national insect survey

Abstract: Monitoring networks are improved by additional sensors. Optimal configurations of sensors give better representations of the process of interest, maximising its exploration while minimising the need for costly infrastructure. By modelling the monitored process, we can identify gaps in its representation, i.e. uncertain predictions, where additional sensors should be located. Here, with data collected from the Rothamsted Insect Survey network, we train an artificial neural network to predict the seasonal aphid … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…Compared with the ecophysiological models, the binary classification ML model showed markedly improved prediction accuracy. Many studies have also demonstrated that the ML phenological model improves the accuracy of phenological prediction (Bourhis et al, 2021; Dai et al, 2019; Holloway et al, 2018; Oses et al, 2020). Based on the comparison of the prediction results of ML regression models for the same species (LUD prediction), the prediction RMSE of the RF regression model on the test set (5.4 days) was greater than that of the GDD model (4.3 days) (Dai et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Compared with the ecophysiological models, the binary classification ML model showed markedly improved prediction accuracy. Many studies have also demonstrated that the ML phenological model improves the accuracy of phenological prediction (Bourhis et al, 2021; Dai et al, 2019; Holloway et al, 2018; Oses et al, 2020). Based on the comparison of the prediction results of ML regression models for the same species (LUD prediction), the prediction RMSE of the RF regression model on the test set (5.4 days) was greater than that of the GDD model (4.3 days) (Dai et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Although this phenological model can facilitate the development of biologically realistic process‐based experimental designs by using phenological observations in natural conditions as the main biological information (Janosi et al, 2020), like other statistical models it still faces great challenges in providing mechanistic explanations for plant growth and development processes (Hänninen, 2016; Hänninen et al, 2019). In ML methods, it is often difficult to relate the predictions to variables directly and to quantify the relationship between labels and features (Bourhis et al, 2021). Although machine learning is statistically advanced, it cannot provide a complete solution.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation